GAMBARAN KADAR LOW DENCITY LIPOPROTEIN (LDL) PADA SISWA-SISWI OVERWEIGHT DAN OBESITAS DI KOTA MANADO - Elim, Christoffel; Pangemanan, Damajanty H.C.; Warouw, Sarah; Supit, Siantan; Lindo, Vellisia (UNIVERSITAS SAM RATULANGI, 2012)
Abstract: Low-density lipoproteins (LDL) are lipoproteins that carry cholesterol to maintain the functions of cells. One factor that can raise the levels of LDL is obesity. In general, obese people have higher triglycerides stored under the skin (subcutaneous). Triglycerides are the main ingredient for the formation of VLDL in the liver. This study aimed to get an overview of the levels of LDL in overweight and obese students at the Pax Christie and Don Bosco junior high schools in Manado. This was a cross sectional analytic study. Samples involved 30 students meeting the inclusion criteria: age 10-15 years, Body Mass Index (BMI) ?23.0, and willing to be respondents with signed parental informed consents. Results: Samples of obese students were 26 (86.7%) and of overweight students four (13.3%). There were six students (20%) who had LDL higher than normal levels (?130 mg/dL). Conclusion: InManado, there were more obese students than overweight students. Some of the students showed LDL higher than normal levels. Keywords: students, overweight, obesity, LDL. Abstrak: Lipoprotein densitas rendah merupakan lipoprotein yang mengangkut kolesterol ke sel-sel tubuh yang memerlukannya, dimana bila kadarnya berlebih tentu akan berpengaruh buruk terhadap kesehatan. Salah satu faktor yang dapat meningkatkan kadar LDL adalah obesitas. Orang gemuk umumnya memiliki kadar trigliserida yang tinggi dan disimpan dibawah kulit. Trigliserida ialah komponen utama yang membentuk lipoprotein densitas sangat rendah (VLDL) di organ hati. Penelitian ini bertujuan untuk mengetahui kadar LDL pada pelajar tingkat dasar Pax Christie dan Don Bosco Manado yang berat badannya berlebih (overweight) dan yang obesitas. Metode penelitian berupa analisis cross-sectional. Sampel sebanyak 30 pelajar dengan kriteria inklusi: umur 10-15 tahun, Indeks Massa Tubuh (IMT) ?23,0, dan bersedia mengikuti penilitan. Hasil penelitian memperlihatkan jumlah sampel yang obes sebanyak 26 pelajar (86,7%) dan yang overwight empat pelajar (13,3%). Terdapat enam pelajar (20%) dengan LDL melebihi nilai normal (?130 mg/dL). Simpulan: Di Kota Manado, jumlah pelajar yang obes melebihi yang overweight. Beberapa di antaranya memperlihatkan kadar LDL melebihi nilai normal. Kata kunci: pelajar, berat badan berlebih, obesitas, LDL.